Engineering an antibody with picomolar affinity to DOTA chelates of multiple radionuclides for pretargeted radioimmunotherapy and imaging - Orcutt, Kelly Davis (2010)
INTRODUCTION: In pretargeted radioimmunotherapy (PRIT), a bifunctional antibody is administered and allowed to pre-localize to tumor cells. Subsequently, a chelated radionuclide is administered and captured by cell-bound antibody while unbound hapten clears rapidly from the body. We aim to engineer high-affinity binders to DOTA chelates for use in PRIT applications. METHODS: We mathematically modeled antibody and hapten pharmacokinetics to analyze hapten tumor retention as a function of hapten binding affinity. Motivated by model predictions, we used directed evolution and yeast surface display to affinity mature the 2D12.5 antibody to 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA), reformatted as a single chain variable fragment (scFv). RESULTS: Modeling predicts that for high antigen density and saturating bsAb dose, a hapten binding affinity of 100 picomolar (pM) is needed for near-maximal hapten retention. We affinity matured 2D12.5 with an initial binding constant of about 10 nanomolar (nM) to DOTA-yttrium chelates. Affinity maturation resulted in a 1000-fold affinity improvement to biotinylated DOTA-yttrium, yielding an 8.2 ± 1.9 picomolar binder. The high-affinity scFv binds DOTA complexes of lutetium and gadolinium with similar picomolar affinity and indium chelates with low nanomolar affinity. When engineered into a bispecific antibody construct targeting carcinoembryonic antigen (CEA), pretargeted high-affinity scFv results in significantly higher tumor retention of a (111)In-DOTA hapten compared to pretargeted wild-type scFv in a xenograft mouse model. CONCLUSIONS: We have engineered a versatile, high-affinity DOTA-chelate-binding scFv. We anticipate it will prove useful in developing pretargeted imaging and therapy protocols to exploit the potential of a variety of radiometals.